1967
DOI: 10.1111/j.1365-2621.1967.tb00846.x
|View full text |Cite
|
Sign up to set email alerts
|

A Probable Flavoring Principle in Vegetable‐Protein Hydrolysates

Abstract: SUMMARY— The characteristic seasoning flavor of hydrolyzed vegetable proteins has previously been attributed to α‐ketobutyric acid formed from threonine under the conditions of acid‐hydrolysis. However, pure α‐ketobutyric acid is virtually odorless and tasteless, and it develops the characteristic flavor only upon ageing. The true flavoring principle is probably α‐hydroxy‐β‐methyl‐Δ.α,β‐γ‐hexenolactone, which is formed from the acid by dimerization, lactonization, and decarboxylation. This conversion occurs sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
2

Year Published

1974
1974
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 20 publications
1
30
0
2
Order By: Relevance
“…The molar ratio of starting materials has an important effect on the yield of HDMF, and the highest yield was obtained from equal molar proportions of threonine and organic acid. In proportion to the decrease in the ratio of organic acid to threonine, the forma tion of 3-hydroxy-4-methyl-5-ethyl-2(5H)-fura none (HMEF) which has been isolated from vegetable-protein hydrolysates by Sulser et al 2) increased, while that of HDMF decreased.…”
Section: Properties Of Bfcmentioning
confidence: 99%
“…The molar ratio of starting materials has an important effect on the yield of HDMF, and the highest yield was obtained from equal molar proportions of threonine and organic acid. In proportion to the decrease in the ratio of organic acid to threonine, the forma tion of 3-hydroxy-4-methyl-5-ethyl-2(5H)-fura none (HMEF) which has been isolated from vegetable-protein hydrolysates by Sulser et al 2) increased, while that of HDMF decreased.…”
Section: Properties Of Bfcmentioning
confidence: 99%
“…20 The results were collected in Table 3. We pleasingly found that β-mono substituted 2-oxocarboxylic esters 1b-d behaved as suitable reactants for this process (Table 3, entries [3][4][5]. This demonstrated that the first homo-aldol reaction and the subsequent ring closure occurred for these substituted 2-oxocarboxylic esters without difficulty.…”
Section: Methodsmentioning
confidence: 92%
“…1,2 This kind of compounds have been isolated from a variety of natural sources, 1,2 and their properties leading to use as flavoring agents, 3 perfumes 4 and anti-depressants 5 have been evaluated, and analgesic 6 and antifungal 7 activities have been documented.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have investigated volatile substances responsible for the flavour of chemically hydrolyzed proteins. Sulser et al [7] found 2-hydroxy-3-methyl-4-ethyl-2-buten-4-olide to be the flavouring principle of this type of products. Many volatile substances were identified by MANLEY et al in basic [8], acidic and neutral [9] fractions from hydrolyzed soy protein.…”
mentioning
confidence: 98%